Spray-dried powders from berries extracts obtained upon several processing steps to improve the bioactive components content - Gagneten, Maite (2019)
This work aimed at developing powders rich in antioxidant compounds and pigments from three berries grown in argentine Patagonia: blackcurrant, raspberry and elderberry. Ultrasound-assisted extraction (UAE) was applied on the precipitates generated after juice production in order to improve bioactive compounds recovery. The best extracts (UAE 10 min for raspberry and blackcurrant, and 5 min for elderberry), obtained after 2–3 extraction cycles were mixed and spray-dried. The glass transition temperatures (43–50 °C), and the low water content (0.92–1.44%) and water activity values (<0.06) of the powders suggest that they could be stored at room temperature without risk of physical deterioration. Elderberry and blackcurrant powders showed good flowability and low cohesiveness while raspberry powders presented an intermediate cohesiveness and fair flowability. This was consistent with the smooth surface and the less shrinkage of the raspberry powder particles observed by microscopy. Elderberry powders presented higher concentration of bioactive compounds (polyphenols content 4.57 ± 0.23 mg gallic acid (GA)/g d.m. and monomeric anthocyanins content 2.39 ± 0.12 mg cyd-3-glu/g d.m.), and higher antioxidant capacity (3.33 ± 0.57 mg GA/ g d.m.) when compared to raspberry and blackcurrant. The obtained powders result possible ingredients to be used as natural colorants or antioxidants.